Sharing economy: Approaches and distances between the notion and the practice of sharing - Ramalho, Francisco Rodolfo Xavier; Rigo, Ariádne Scalfoni (Contextus - Revista Contemporânea de Economia e Gestão, 2020)
This work aims to analyze the existing approaches and distances between sharing and what is practiced by users of organizations in the sharing economy. Sharing practices in two organizations were studied: Airbnb and Servas. Mauss' gift theory was used as a lens of analysis. Interviews were conducted with users / members of both organizations and content analysis was undertaken. Results revealed, while in Servas, there is a great similarity between sharing and the practices found in it, in Airbnb there is a certain distance. It is suggested to use terms and expressions that best represent the practices of organizations inserted in the sharing economy.